Implementation of Panch Kekaar And Khalsa In Sikh Society In Kelantan, Malaysia. - Md. Zain, Aman Daima; Syed Omar, Syed Hadzrullathfi; Othman, Mohd Shahril; Mohamed, Hasan Al-Banna (2011)
The Khalsa and the Panch Kekaar arc the two main elements in Sikhism. Those who want to become a member of this group must respect some symbols of the Sikhism called Panch Kekaar which consists of five, namely Kes (hair). Kara (iron bracelet). Kangha (brush), Kachera (trouser) and Kirpan (sword). In order to see its significance in the Sikhism, a study of the Sikh community in Kelantan has been made and it is discovered that the respondents were less satisfacticd with Panch Kekaar. The study also found that not many of them fully exercise the Panch Kekaar in their lives.